The concept of maternal care quality for women with low-risk pregnancy in the maternity ward: An integrative review - Zohreh Khakbazan; Maryam Damghanian; Armin Zareiyan; Fatemeh Abbaszadeh (Kashan University of Medical Sciences, 2022)
Background: Improving the quality of maternal care is considered a key strategy for improving maternal and neonatal outcomes. However, available definitions do not clearly define this concept. Objective: The aim of this study was to clarify the concept of maternal care quality (MCQ) for women with low-risk pregnancy in the maternity ward and to determine its attributes. Methods: This integrative review was conducted using Whitmore and Knafl's method. An online literature search was done in Medline, Embase, Web of Sciences, Scopus, SID, Magiran, and IranMedex databases as well as the websites of health-care and midwifery organizations and associations. Data were analyzed in the four steps of data reduction, data display, data comparison, and conclusion drawing and verification. Results: The two main attributes of MCQ are effective communication and interaction and professional care. Effective communication and interaction between the care provider and pregnant women in the maternity ward is the most important attribute of MCQ. The first category included three subcategories, namely informational interaction, human interaction, and participatory interaction. The two subcategories of the second category were adherence to standards during care delivery and delivering accessible care. Conclusion: MCQ in maternity ward is defined as "the process of delivering safe, fair, accessible, and standard professional care to women during childbirth through human, informational, and participatory interactions."